Investigation on the Effect of Gain Medium on the Performance of Double-pass Raman Amplifier - Hamzah, Azura; Huri, N.A.D.; Emami, Siamak Dawazdah; Harun, Sulaiman Wadi; Ahmad, Harith (De Gruyter, 2010)
The Raman gain characteristics of the double-pass Raman amplifier (RA) is investigated for different gain medium. The double-pass operation is obtained by using an optical circulator at the end the gain medium to act as a loop mirror. The double-pass RA is experimentally demonstrated to enhance an on/off gain characteristic when compared to the conventional single pass system. By using a piece 20 km long non-zero dispersionshifted fiber (NZ-DSF) as the gain medium, maximum on/off gain of 23 dB is achieved in 1600 nm region using 350 mW of 1490 nm pump power. It is also observed that the backward pumping demonstrates a slightly better gain compared to that of forward pumping for the double-pass RA.